Alla scoperta dell’Italia e degli italiani: Zavattini e altri autori (1944-1963) - Falaschi, Giovanni (Cuadernos de Filología Italiana, 2007)
After the fall of Fascism Italian intellectuals suddenly discovered their own country and their fellowcitizens, whom they only knew from the Fascist propaganda. Cinema, photography, reportage, prose narrative: all these techniques were used to understand the country that had lost the war. In the mid-Fifties a booming economy transformed Italy again. This survey considers the years 1944-1963, and looks in particular at the following authors: C.Levi, Pasolini, Calvino, Piovene, Bocca, Bianciardi, Mastronardi; and first of all, with a deeper insight, Zavattini.